Exploring the Application of Metacognitive Strategy in Chinese Writing in Middle Schools - Li, Zhoutong (Transactions on Social Science, Education and Humanities Research, 2024)
Metacognitive strategy, one of the strategies of learning languages, is essential for learning Chinese writing. The research is conducted by analyzing the relationship between the levels of middle-school students using metacognitive strategy and their levels of Chinese writing. The results of the research indicate significant correlation exists between levels of Chinese writing and the levels of middle-school students using metacognitive strategy. During the examination phase, students tend to use metacognitive strategy before the commencement of writing and the level of using strategy in daily study is much lower than it is in the examination phase. The degree of impact of strategies on Chinese writing in middle schools, in descending order, is monitoring strategy, adjustment strategy and planning strategy. However, the difference in impact on writing levels among such three strategies is small. According to the results, teachers should design conscious training to teach middle-school students to use metacognitive strategy effectively and enhance their abilities of using metacognitive strategy in daily study. Moreover, coordinating the intensity of the teaching monitoring strategy, adjustment strategy and planning strategy is important.